PHYSICAL QUALITY AND ORGANOLEPTICS OF MARINATED BROILER MEAT WITH ROSELLA FLOWER EXTRACT (Hibiscus sabdariffa Linn) - D. M., Barus; Umiarti, A. T.; Okarini, I. A. (Jurnal Peternakan Tropika, 2022)
Rosella flower (Hibiscus sabdariffa Linn) is one of the plants that is used as a preservative because it contains antioxidants and antibacterial.  This research was conducted to determine the physical and organoleptic qualities of broiler meat marinated with rosella flower extract (Hibiscus sabdariffa Linn) . This research was carried out in March 2021 at the Animal Products Technology Laboratory (ENT) of the Faculty of Animal Husbandry, Udayana University. The experimental design used was a completely randomized design (CRD) with four treatments and four replications in order to obtain 16 experimental units. The four treatments were: (P0) 100 grams of broiler meat without marinating or control, (P1) 100 grams of broiler meat marinated with 3% rosella flower extract, (P2) 100 grams of broiler meat marinated with rosella flower extract 6%, (P3) 100 grams of broiler meat marinated with 9% rosella flower extract, the duration of the marinade for all treatments was 30 minutes. The variables observed were the physical quality of pH, cooking loss, water holding capacity and organoleptic quality, namely color, aroma, texture and taste. The results showed that the 30 minute marinade with rosella flower extract up to 9% showed significantly different results (P<0.05) at the pH of the treatment P0 with P2, P0 with P3 and P1 with P2. Based on the results of this study, it can be concluded that 30 minutes of marinating with rosella flower extract up to 9% can reduce the pH value. The best pH was obtained in the P2 treatment (6%) while the cooking loss, water holding capacity and organoleptic got the same results in all treatments. Keywords: Rosella flower, broiler meat, physical quality, marinated, organoleptic test